2014
DOI: 10.4103/0974-620x.142593
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual angle on pattern reversal visual evoked potentials

Abstract: Purpose:The aim of this study was to find whether the visual evoked potential (VEP) latencies and amplitude are altered with different visual angles in healthy adult volunteers or not and to determine the visual angle which is the optimum and most appropriate among a wide range of check sizes for the reliable interpretation of pattern reversal VEPs (PRVEPs).Materials and Methods:The present study was conducted on 40 healthy volunteers. The subjects were divided into two groups. One group consisted of 20 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In contrast, Kathari et al, (15) found statistically significant difference of amplitude of N135 for the checks (15', 30' and 120'),and observed that high value of mean P100 amplitude for usual angle 15' and when the angle increased to 30' a drop of P100 amplitude was obtained with increasing check size.…”
Section: Discussion:-mentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, Kathari et al, (15) found statistically significant difference of amplitude of N135 for the checks (15', 30' and 120'),and observed that high value of mean P100 amplitude for usual angle 15' and when the angle increased to 30' a drop of P100 amplitude was obtained with increasing check size.…”
Section: Discussion:-mentioning
confidence: 83%
“…On comparison between blue and white FVEP in latencies and amplitudes (COVinter) and (COVintra ) were less for blue FVEP than for white FVEP, this means that blue light has less variability. Concerning PRVEP, the mean latencies of (N75, P100, N135) and amplitudes of (N75-P100) and (P100-N135) using four different check sizes (15,30, 60 and 120) minutes of arc and the obtained results are tabulated in table (5,6) and summarized by histograms in figure (7,8) respectively .The mean of all latencies were decreased with increase of check size and the amplitudes were increased when the check size increase. It is to be noted that the most suitable visual angle was 120'.…”
Section: Results:-mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the 15 min check size had revealed additional information than the 1 degree check size and that could delineate the different area of perception of both check sizes. The Large check sizes 1 degree (60 min) mainly perceive signals from the peripheral field outside the central 3º but not beyond 10º of the visual field Phurailatpam, 2014, while smaller check sizes mainly perceive signal from the foveal area (central visual field) Kothari et al, 2014. Jancic et al, 2016 demonstrated that the responses to smaller checks are more sensitive to disorders of the visual pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Magnocellular (M pathway), which is sensitive to low spatial frequency (large checks) and parvocellular ( P pathway), which is more sensitive to high spatial frequency (small checks). Kothari et al, 2014 ;Abdelkader, 2016. VEPs are influenced by optic nerve diseases, demyelinating processes, disorders of either subcortical or cortical neurons of brain hemispheres, metabolic abnormalities, traumatic brain injury and the use of psychoactive medications. Amodio & Montagnese,2015, the magnitude of the PVEP abnormality is correlated with other measures of injury severity such as the extent of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%